2020
DOI: 10.1016/j.bpj.2019.11.768
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Pharmacological Characterization of C. elegans DEG/ENaC/ASIC Channels

Abstract: Pregnenolone (PREG) is a neurosteroid that modulates several brain functions, neuronal firing, glial growth and differentiation, these effects being primarily attributed to PREG actions on the neurons and glial cells. Despite the vital role of the cerebral circulation for brain function and the fact that PREG is a vasoactive agent, PREG actions on cerebral artery function remain unknown. Thus, we first obtained a concentration response curve to PREG on the diameter of de-endothelialized, in vitropressurized mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, degenerins (DEG) are C. elegans specific ion channels characterized for the unusual gain-offunction mutations which induce degenerations like swelling, vacuolation and eventually cell death (Hall et al, 1997). So far, about 30 genes encoding DEG/ENaC superfamily have been discovered in the C. elegans genome (Fechner et al, 2020). Studies in mechanoreceptor currents of DEG/ENaC channels revealed similarities to mechanoelectrical transduction of gentle and nociceptive mechanical stimuli.…”
Section: Deg/enac Channelsmentioning
confidence: 99%
“…In contrast, degenerins (DEG) are C. elegans specific ion channels characterized for the unusual gain-offunction mutations which induce degenerations like swelling, vacuolation and eventually cell death (Hall et al, 1997). So far, about 30 genes encoding DEG/ENaC superfamily have been discovered in the C. elegans genome (Fechner et al, 2020). Studies in mechanoreceptor currents of DEG/ENaC channels revealed similarities to mechanoelectrical transduction of gentle and nociceptive mechanical stimuli.…”
Section: Deg/enac Channelsmentioning
confidence: 99%